2021
DOI: 10.3389/fmolb.2021.654866
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ribosome Activity on SARS-CoV-2 LNP – Based mRNA Vaccines

Abstract: Coronavirus-related Severe Acute Respiratory Syndrome-2 (SARS-CoV-2) initially was detected in Wuhan, Hubei, China. Since early 2021, World Health Organization (WHO) has declared Coronavirus Disease 2019 (COVID-19) a pandemic due to rapidly transformed to a globally massive catastrophic viral infection. In order to confront this emergency situation, many pharmaceutical companies focused on the design and development of efficient vaccines that are considered necessary for providing a level of normalization in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Animal experiments have shown that adenovirus-vector DNA can remain detectable for months after inoculation in transcriptionally active form 82 in contrast to rapidly degraded RNA 55 , 83 . Persistence of antigen expression may be a distinctive feature of adenovirus vector vaccines, and has been proposed to contribute to induction of sustained immune responses and long-lasting immunity (reviewed in 41 ).…”
Section: Vaccine-specific Differences Of S-antigen Structure and Presentationmentioning
confidence: 99%
“…Animal experiments have shown that adenovirus-vector DNA can remain detectable for months after inoculation in transcriptionally active form 82 in contrast to rapidly degraded RNA 55 , 83 . Persistence of antigen expression may be a distinctive feature of adenovirus vector vaccines, and has been proposed to contribute to induction of sustained immune responses and long-lasting immunity (reviewed in 41 ).…”
Section: Vaccine-specific Differences Of S-antigen Structure and Presentationmentioning
confidence: 99%
“…Understanding the molecular significance of these different viral strains is a crucial step for designing and implementing rational and effective anti-SARS-CoV-2 strategies. For this reason, many pharmaceutical companies worldwide invest in the development of monoclonal antibodies (mAbs) and vaccines based on different platforms including, DNA plasmid based and also innovative nucleoside-modified viral messenger RNA encapsulated within nanoparticles -specifically lipid ones (LNPs) ( Lee et al, 2020 , Tsiambas et al, 2021 , Jackson et al, 2020 ). Efficient vaccines and mAbs are considered necessary in order normalization and restoration of disrupted global human social-economical activity to be established ( Flanagan et al, 2020 ; Dai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of these genes may impair the ribosome biogenesis process and affect protein synthesis [ 44 ]. This may have various effects on the body, including a decrease in the production of immune-related proteins and an impairment in the response to viral infections [ 45 ]. Additionally, these hub genes have been associated with various biological processes, including translation, cytoplasmic translation, mRNA splicing, and rRNA processing.…”
Section: Discussionmentioning
confidence: 99%